Utilization of Beliefs and Food Taboos in The ’Horse-Man’ Myth as BIPA Learning Content in East-Timor - Bera, Elisabeth Merniana; Idris, Nuny Sulistiany; Sundusiah, Suci (Jurusan Tadris Bahasa Indonesia, 2025)
This research analyzes the